Evaluation Report on Working of Community Projects During the Six Months October 1953 - March 1954 - Planning Commission (Planning Commission, 1953)
The first evaluation report on the progress of community projects for the year ending September 1953 was presented in May 1954. The second year of community projects development is also now over. It will be some time before the second annual report will be available. In the meanwhile, the third, which according to the original programme is the last year of the working of these community projects has commenced. If, therefore, the experience gained hitherto is to be of some immediate use an interim report on a shorter period is called for. Accordingly, a brief report on the work of community projects, principally as represented by the six monthly (October 1953 to March 1954) progress of the several evaluation centres, has been prepared. It does not seek in any way to anticipate the second annual report, but even as it stands it has several features of interest for those when are responsible for planning and guiding the progress of community projects. The report is divided into two parts. the first part contains the general report and composite tables of budget, staff and activities relating to the 19 projects and blocks under intensive evaluation. the second part contains reports on progress of individual programmes received from the evaluation centres. This programme-wise presentation has been made in order that a comparative idea of the progress of individual programmes in different areas, and the problems being experienced in each programme may be more easily obtained.
Evaluation Report on Working of Community Projects During the Six Months October 1953 - March 1954
Government of India